The innovative role of public utilities: a strategy for local development - Immacolata Caruso; Tiziana Vitolo; Livia Cocchis (European Regional Science Association (ERSA), 2003)
Reorganisation policies in the field of water management, in Italy, are an interesting issue to analyse, in order to evaluate the new role of public utilities in an innovative and complex strategy for local development. The core of the reform, started with “Legge Galli” (Law 36 of 1994), is the delicate balance between the public administration role of promotion and check, and the private sector role of implementation of investments and management of new water agencies. Due to the crucial role of networking strategies between local authorities and industries, the success of the Galli Reform will be the success of a innovative strategy of local development, in which co-operative linkages, management innovation, technology transfer and advanced training will be the basic tools. All these issues are crucial in Southern Italy, particularly in Campania, a region that policy of European Union classified as “Ob. 1” (under-developed region), for the high levels of unemployment. The analysis of the Campania's “Regional Operative Plan” for 2000-2006, shows, above all in the field of water management, the choice of a strategy of local development, linking together public and private sector. In fact, the “Regional Operative Plan” for Campania give to private sector a crucial role fort the fund raising for the implementation of the reform, in co-operation with public funds. In this perspective, new organisational strategies and price policies are very important, but the core of the management innovation choice is the role of project financing. Another key question is the protection of local environment and the correct management of water supply and demand. The adoption of these innovative strategies in the field of public utilities are functional to a new policy of local development, based on participation, cost and responsibility sharing among all the actors of local innovation system. Key question of the Italian reform of the water management sector are common to all the Italian public utilities sector, that, in recent years, has been living an important evolution towards new management models balancing economic efficiency and public welfare.
Keywords: 330